Factors Driving the Quality of Financial Reporting in Non-Financial Public Companies in Indonesia - Irawan, Kenny; Dyna Rachmawati; Silvarajoo, Eindresvari A/P (Journal of Accounting Science, 2025)
General Background: Financial reporting quality (FRQ) is critical to stakeholders, as it supports making informed economic decisions based on reliable corporate financial statements. Specific Background: The cases of fraudulent reporting committed by PT Garuda Indonesia Tbk (2019) and PT Asuransi Jiwasraya (2021) underscore the urgency to ensure financial statements reflect a true and fair view. Knowledge Gaps: Existing literature lacks a comprehensive approach that integrates various models and non-financial determinants, such as Environmental, Social, and Governance (ESG) factors, in assessing FRQ. Objectives: This study aims to examine the effect of corporate governance mechanisms, financial leverage, audit quality, and ESG performance on FRQ, with firm size as a control variable. Methods: Using four regression models and multiple proxies for FRQ, this study adopts a robust empirical design. Results: Findings reveal mixed effects: corporate governance has a positive effect on FRQ in one model; audit quality shows no effect or is negative; financial leverage is insignificant; ESG performance varies from positive, negative, to no effect. Model 2 showed the highest explanatory power, supporting the relevance of ESG and governance to FRQs. Novelty: This study introduces a multi-model, multi-proxy framework and diversifies ESG measurement sources to enrich the depth of analysis. Implications: For practitioners, ESG engagement and governance compliance signal improved FRQ, guide investment and lending decisions and provide direction for future research.